2010
DOI: 10.1177/147323001003800616
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Cannabinoid Receptor 2 Selective Antagonist on the Inflammatory Reaction to Titanium Particles In Vivo and In Vitro

Abstract: Wear particle-induced inflammation is a major factor contributing to aseptic loosening in peri-prosthetic tissue. The effects of cannabinoid receptor 2 (CB(2)) on wear particle-induced inflammation remain unclear. Reverse transcription-polymerase chain reaction and enzyme-linked immunosorbent assay were used to assess the effects of a CB(2)-selective antagonist, AM630, on regulation of the inflammatory reaction and production of pro-inflammatory cytokines in response to in vitro and in vivo stimulation with ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…However, Bzb may inhibit inflammatory response at both of the two stages without disturbing the basal secretion of these cytokines. The secretion profiles of TNF-α and IL-1 reported here are consistent with some reports [28], but they differ from those of Zhou et al [29] who found that the elevated secretion of TNF-α can continue up to day 14 after Ti injection. Different physical characteristics of the particles and different drug interventions may account for these differences.…”
Section: Discussionsupporting
confidence: 75%
“…However, Bzb may inhibit inflammatory response at both of the two stages without disturbing the basal secretion of these cytokines. The secretion profiles of TNF-α and IL-1 reported here are consistent with some reports [28], but they differ from those of Zhou et al [29] who found that the elevated secretion of TNF-α can continue up to day 14 after Ti injection. Different physical characteristics of the particles and different drug interventions may account for these differences.…”
Section: Discussionsupporting
confidence: 75%
“…Small particles are easily phagocytosed, but they cannot be digested. Phagocytes in the tissue around the implant site engulf wear particles, which results in activated cells that secrete high levels of inflammatory cytokines such as TNF-a and IL-1b, both of which promote osteoclastogenesis and, eventually, contribute to the osteolytic process [32,33]. In a macrophage depletion mouse model TNF-a and IL-1b expression was significantly reduced, as was the number of TRAP + cells in pouch tissues [34].…”
Section: Discussionmentioning
confidence: 99%
“…Some cytokine inhibitors have been investigated using in vitro and in vivo animal models. Potential treatments include the following.AM630 is a selective inhibitor of cannabinoid receptor 2 that inhibits IL-1 β and TNF- α [69]. …”
Section: Therapy Of Aseptic Loosening By Regulation Of the Innate mentioning
confidence: 99%